2009
DOI: 10.1177/0363546509347985
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Running-Related Injuries in Novice Runners Enrolled in a Systematic Training Program

Abstract: Male and female novice runners have different risk profiles. Higher BMI, previous injury, and previous sports participation without axial loading are important predictors for RRI in male participants. Further research is needed to detect more predictors for female novice runners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
216
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(232 citation statements)
references
References 28 publications
5
216
2
9
Order By: Relevance
“…Running-related injuries such as medial tibial stress syndrome (''shin splints''), patellofemoral pain syndrome (''runner's knee''), Achilles tendonitis, plantar fasciitis, and iliotibial band syndrome have been reported to affect approximately 20-79% of runners on an annual basis [1,2]. Unfortunately, the etiology of running-related injuries is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Running-related injuries such as medial tibial stress syndrome (''shin splints''), patellofemoral pain syndrome (''runner's knee''), Achilles tendonitis, plantar fasciitis, and iliotibial band syndrome have been reported to affect approximately 20-79% of runners on an annual basis [1,2]. Unfortunately, the etiology of running-related injuries is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the etiology of running-related injuries is not well understood. Previous research has reported that increasing age, female gender, previous injury, high BMI, low fitness level, foot posture, and excessive training distance are associated with injury [1][2][3]. Previous research has also suggested that pronation or pronation rate may be associated with injury [4,5], and this belief has led to the development of running shoes aimed at reducing pronation (e.g., motion control shoes).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the incidence of running injuries has increased, especially to the lower extremity [1]. Most of the running injuries are overuse injuries which occur as a result of repetitive microtrauma from chronic submaximal loading of tendons, muscles, or bones.…”
Section: Introductionmentioning
confidence: 99%
“…It is stated that biomechanical, hormone and neuromuscular factors play a crucial role in the onset of injuries 21,22 . In the present study, there were no differences between genders.…”
Section: Discussionmentioning
confidence: 99%